A study on the effect of psychological characteristics on aviation safety - Choi, Jeongyeol (Korean Journal of Industrial and Organizational Psychology, 2014)
This study aims to reveal what personal characteristics are related to aviation accidents. For this purpose, the individual’s psychological traits revealed in the previous studies are classified in the aspect of personality, attitude, emotion, cognition and physical condition and questionnaires are designed accordingly. It carried out group mean test and Logistic Regression on the response data from 140 ROK Air Force pilots. The result of the mean test showed no characteristics that distinguish the ones who experienced aviation safety risk from the ones who did not, but it revealed that the distinct characteristics between the ones who violated ROE regulation and the ones who did not consist of two factors of conscientiousness and chronic stress. The result showed significant differences between the aviation incidents experience group and inexperience group in 11 characteristic factors of risk seeking, risk acceptance, lack of discipline, neglect of warning, anxiety, depression tendency, inattention, vigilance, risk sensitivity, forthrightness, and chronic fatigue/condition. Between the Near Miss/ACAS experience group and inexperience group, the mean test showed differences in 4 characteristic factors of anxiety, inattention, risk acceptance and chronic stress. The result of Logistic Regression indicated that the characteristic factors that distinguish the incident experience group from the incident inexperience group with high predictability are 4 factors consist of risk sensitivity, chronic fatigue/condition, anxiety, and depression tendency, and the factor that distinguish the Near Miss/ACAS experience group from the Near Miss/ACAS inexperience group turned out to be anxiety. The present study has significance in disclosing the pilot characteristic factors related to aviation accident or risk by taking pilots as test subject. The result of the study is discussed in light of its theoretical and practical implications as well as its restrictions.